Promoting effect of panaxatriol ginsenoside on gene expression of human interleukin-1 - Tian Zhi-Gang; Yang Gui-Zhen (Acta Pharmacologica Sinica; Vol 14, No 2 (March 1993): Acta Pharmacologica Sinica, 2016)
Effect of panaxatriol ginsenoside (PG) on interleukin-1 (IL-1) gene expression was studied by using wheat germ extract (cell-free translation system) and IL-1 bioassay. The results showed that IL-1 production increased by 40% (487-682 U.ml-1) at maximum during cell culture (0-84 h) after PG (10 micrograms.ml-1) was added to phytohemagglutinin (PHA, 50 micrograms.ml-1) stimulated lymph node cells. Meanwhile, IL-1 mRNA from PHA combined with PG stimulated lymph node cells translated 39.5% more IL-1 than that of PHA-stimulated cells at maximum (2500-3489 U/mg RNA).